2008
DOI: 10.1080/02699200701799684
|View full text |Cite
|
Sign up to set email alerts
|

Tongue palate contact patterns of velar stops in normal adult English speakers

Abstract: This paper provides a more detailed description of normal tongue palate contact patterns for the occlusion phase of velar stops than currently exists. The study used electropalatography (EPG) to record seven normally speaking adults' contact patterns of voiceless velar stops in nine VkV contexts. A variety of EPG indices measured: per cent complete closures across the palate; place of articulation; articulatory distance between /k/ and /t/; and amount of contact. Complete EPG closure occurred in the majority (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…For example, conducted a study on normal alveolar stops and found that although all the speakers produced similar "horse-shoe" spatial patterns for these targets, some speakers had more than twice as much contact as others. Studies of typical velars (Liker & Gibbon, 2008), bilabials , vowels (Gibbon, Lee, & Yuen, 2010) and affricates (Liker et al, 2007) had similar results insofar as some speakers had twice or three times more contact than others. One explanation for this variation is that the amount of contact relates to inter speaker differences in palatal shape.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…For example, conducted a study on normal alveolar stops and found that although all the speakers produced similar "horse-shoe" spatial patterns for these targets, some speakers had more than twice as much contact as others. Studies of typical velars (Liker & Gibbon, 2008), bilabials , vowels (Gibbon, Lee, & Yuen, 2010) and affricates (Liker et al, 2007) had similar results insofar as some speakers had twice or three times more contact than others. One explanation for this variation is that the amount of contact relates to inter speaker differences in palatal shape.…”
supporting
confidence: 62%
“…A number of recent EPG studies confirm that, even in typical adults and children, there is a wide variation between speakers in EPG index values for any given target sound (Cheng, Murdoch, Goozee, & Scott, 2007;Gibbon, Yuen, Lee, & Adams, 2007;Liker & Gibbon, 2008;Liker, Gibbon, Wrench, & Horga, 2007;McLeod, Roberts, & Sita, 2006). For example, conducted a study on normal alveolar stops and found that although all the speakers produced similar "horse-shoe" spatial patterns for these targets, some speakers had more than twice as much contact as others.…”
mentioning
confidence: 87%
“…Despite gaps in tongue-palate contact in the velar region, it is possible that the tongue body raising gesture occurred but could not be measured by EPG alone. Liker and Gibbon (2008) suggest that closure does occur in these cases but in a location posterior to the area covered by the EPG electrodes. It is also possible, of course, that the incomplete closure observed in the linguapalatal contact patterns indicates a laxer articulation of the velar consonant.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that instances of partial assimilation in normal adult speech involve a reduced coronal gesture which results in the lateral contact with the hard palate observed here (Ellis and Hardcastle, 2002). The retracted production of velar plosives has been observed in connected speech in adults in both single syllable production (Liker and Gibbon, 2008) and connected speech (Hardcastle, 1994), and in other children with speech difficulties (Howard, 2004) and is likely to reflect inter-and intra-speaker variation. Despite gaps in tongue-palate contact in the velar region, it is possible that the tongue body raising gesture occurred but could not be measured by EPG alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is desirable to have multiple repetitions of speech material due to intra-speaker variability and to record an adequately sized group of speakers due to inter-speaker variability. In terms of variability in amount of contact, recent studies have shown that although typical speakers produce similar contact patterns for target sounds, some speakers can have up to twice as much contact as others (Cheng et al, 2007;Liker et al, 2007;Liker and Gibbon, 2008).…”
Section: Introductionmentioning
confidence: 99%